Evaluation of the glomerular filtration rate in elderly hospitalized patients using antimicrobials (Research, Society and Development, 2022)
With population aging, there is a high prevalence of non-communicable chronic diseases, with frequent hospitalization of the elderly due to the aggravation of some of these pathologies. It is common that, at some moment during hospitalization, these patients use antimicrobials (ATB), whose use needs to be properly monitored in order to minimize harmful effects resulting from this treatment. Thus, monitoring the glomerular filtration rate (GFR) is important to detect possible changes in the patient's renal function induced by the use of ATB. In this context, this study aimed to evaluate GFR during treatment with ATB in hospitalized elderly patients. This is an observational study with a retrospective design, which the electronic medical records of elderly patients hospitalized in the medical, neurological, surgical and COVID-19 clinics, who used 1 or more ATB, were analyzed. The results showed that there was a significant reduction in GFR in elderly people who used 2 or more ATB (p=0.022). Thus, it can be concluded that antibiotic therapy may be associated with a reduction in GFR in hospitalized elderly, reinforcing the need for pharmacotherapeutic follow-up, with the aim of optimizing therapy and avoiding side effects such as kidney damage.